Evaluating methods to explore antibiotic use on smallholding pig farms in peri-urban Kenya - Claire Scott; Nicholas Bor; Kristen Klara Reyher; Alex J. Tasker; Henry Buller; Max Korir; Dishon M. Muloi; Dishon M. Muloi; Irene Bueno; Lian Francesca Thomas; Lian Francesca Thomas; Lian Francesca Thomas (Frontiers in Veterinary Science)
BackgroundUnderstanding patterns and practices of antibiotic use (ABU) in livestock is crucial to make informed recommendations for improved antibiotic stewardship and to measure the impact of interventions aimed at reducing inappropriate ABU. In the absence of a unified tool to determine ABU at the farm level, we aimed to enhance the understanding of methodological approaches used to explore ABU by evaluating the strengths and limitations of four different methods on smallholding pig farms in a peri-urban area of Nairobi, Kenya.MethodsABU collection methods were trialed in parallel over one month on 13 farms. We evaluated four methods for their effectiveness in collecting instances of ABU and facilitating further exploration of ABU practices using qualitative discussion. The methods were: waste bucket analysis; medicine-recording sheets; weekly semi-structured interviews; and the “Drug Bag” medicine sorting technique.ResultsWe found that no single method captured all likely or reported instances of ABU. Waste bucket analysis collected the lowest number of instances of reported ABU. The “Drug Bag” collected the highest number of instances but risked over-reporting due to misrecognition, duplication, and recall errors. Contextual factors, such as ABU practices specific to the study context, affected methodological success. An example of this was individual animal treatments being the mainstay of antibiotic use, meaning that empty packaging was not available for the waste bucket. The use of multiple methods in parallel and qualitative data collection was helpful in ascertaining the likelihood of over- or under-reporting of ABU and allowed us to gather a more detailed understanding of ABU practices.DiscussionOur results highlight the challenges of gathering accurate farm-level ABU data. Future studies must consider methodological suitability when planning data collection; we recommend that methodological suitability statements should be included in future publications. Triangulation of methods and qualitative data collection should be employed where possible. Comparative analyses between ABU studies should be carefully structured to account for both methodological and contextual variation.